Association of hemoglobin during pregnancy and maternal and newborn characteristics - Vasquez Vasquez, Javier (2015)
Objetive: To determine the association of pregnant women hemoglobin levels and some maternal and newborn characteristics. Design: Retrospective, observational and correlation study. Setting: Hospital Regional de Loreto, Peru, a teaching hospital. Participants: Pregnant women and their newborns. Interventions: The sample included 320 pregnant women, and we used simple randomized system and an instrument elaborated by the investigators. Main outcome measures: Hemoglobin levels in both mother and her newborn. Results: Average mother’s age was 24 years with high school education, and most were housewife, multiparous and lived together with their partners. Hemoglobin levels in the second trimester were 11-13 g/dL (72,2%) and 9-10 g/dL (27,2%), average 11,4. In the third trimester, patients with hemoglobin values 11-13 g/dL increased to 96,6%, but with same 11,4 g/ dL average. From all pregnant women 93,8% had prenatal control and 61,5% reported more than 4 controls; 12,5% had urinary tract infection. In regards to newborns, 60% were male, 90,9% had Apgar 7-10 at the first minute and 97,8% at 5 minutes. Gestational age by Capurro’s method was 38 to 42 weeks in 86,9%, weight 1 075-4 600 g, 2 997 g + 519 g average; 93,8% were adequate for gestational age, with p not significant in all these parameters. There was statistical significance between low hemoglobin and both more parity (p=0,019) and less weight/ gestational age (p= 0,019). Conclusions: There was statistical significance between hemoglobin levels and both parity (p=0,019) and less weight/gestational age (p=0,019).